(untitled) (Scottish Historical and Archaeological Internet Reports, 2026)
An open area excavation was undertaken at Loak Farm, Bankfoot, Perth and Kinross in 2019 in advance of a borrow pit being opened to supply stone for work on the A9 dualling project. The excavation uncovered seven roundhouses, eight four-post structures, two six-post structures, two ring ditches, an oval post-built structure, a lightweight post-built structure, a post- and post-trench structure, and numerous isolated pits and groups of pits. Radiocarbon dating places the majority of these features in the Late Bronze Age and Iron Age, indicating that the site was a fairly extensive settlement of later prehistoric date. A small assemblage of pottery and coarse stone tools was recovered; the stone tools indicated some limited craftworking activities were taking place at the site. Several features, including a corn-drying kiln and possible field oven, and pits containing ironsmithing evidence, returned dates in the very early medieval period, indicating some reuse of the settlement into the second half of the first millennium AD.